Relasi Filsafat dan Ilmu Pengetahuan dan Realisasinya di Era Super Smart Society - Sari, Ambar; Triatmo, Agus Wahyu (Lembaga Yasin AlSys, 2024)
The relationship between the philosophy of science and education plays a crucial role in shaping the capacity of future generations to think critically and solve problems effectively. Philosophy of science, as a discipline that explores the foundations, methods, and implications of scientific knowledge, offers a framework for understanding how knowledge is constructed and how it can be applied in solving real-world problems. In the context of education, it serves as a cornerstone for fostering analytical thinking, logical reasoning, and reflective inquiry. This paper examines how philosophical perspectives on science can inform educational practices that nurture critical and solution-oriented thinking. By integrating philosophical insights into the curriculum, educators can promote an environment that encourages students to question assumptions, evaluate evidence, and develop innovative solutions to contemporary challenges. Ultimately, the integration of philosophy of science into education not only enhances intellectual growth but also equips students with the tools needed to address the complex issues facing society today. This relationship is essential in preparing a generation that is capable of navigating the rapidly changing world with a mindset grounded in inquiry, adaptability, and ethical reasoning.